2021
DOI: 10.1001/jamasurg.2020.6265
|View full text |Cite
|
Sign up to set email alerts
|

Postdischarge Virtual Visits for Low-risk Surgeries

Abstract: video-based virtual visits are a growing aspect of surgical care and have dramatically increased in the setting of the coronavirus disease 2019 (COVID-19) pandemic.OBJECTIVE To evaluate the outcomes of all-cause 30-day hospital encounter proportion among patients who have a postdischarge video-based virtual visit follow-up compared with in-person follow-up.DESIGN, SETTING, AND PARTICIPANTS Randomized, active, controlled noninferiority trial in an urban setting, including patients from a small community hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…We were not able to measure outcomes. However, in a randomized trial comparing video based or in-person postoperative visits for laparoscopic appendectomy or laparoscopic cholecystectomy, the primary outcome of a 30-day hospital encounter was noninferior ( 36 ). In a larger narrative review of the use of telemedicine in surgical clinics, seven studies showed no statistical difference in complication rates for low-risk surgical patients who had an in-person follow-up compared to telemedicine visit ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to measure outcomes. However, in a randomized trial comparing video based or in-person postoperative visits for laparoscopic appendectomy or laparoscopic cholecystectomy, the primary outcome of a 30-day hospital encounter was noninferior ( 36 ). In a larger narrative review of the use of telemedicine in surgical clinics, seven studies showed no statistical difference in complication rates for low-risk surgical patients who had an in-person follow-up compared to telemedicine visit ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no operative delays were noted in these telehealth-evaluated patients on the day of surgery 3 . Several general surgery and urology studies have demonstrated that telehealth postoperative visits are safe, efficient, and improve patient satisfaction 4–8 …”
mentioning
confidence: 93%
“…2 Telehealth communication technology has been shown as a feasible modality for perioperative care in multiple surgical fields. [3][4][5][6][7][8] Patients report no difference in satisfaction when telehealth is used for preoperative anesthesia evaluations compared with in-person evaluation. 3 In addition, no operative delays were noted in these telehealth-evaluated patients on the day of surgery.…”
mentioning
confidence: 99%
See 2 more Smart Citations